Language, Dementia and Meaning Making Navigating Challenges of Cognition and Face in Everyday Life - Hamilton, Heidi E. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book investigates the ways in which context shapes how cognitive challenges and strengths are navigated and how these actions impact the self-esteem of individuals with dementia and their conversational partners. The author examines both the language used and face maintenance in everyday social interaction through the lens of epistemic discourse analysis. In doing so, this work reveals how changes in cognition may impact the faces of these individuals, leading some to feel ashamed, anxious, or angry, others to feel patronized, infantilized, or overly dependent, and still others to feel threatened in both ways. It further examines how discursive choices made by healthy interactional partners can minimize or exacerbate these feelings. This path-breaking work will provide important insights for students and scholars of sociolinguistics, applied linguistics, medical anthropology, and health communication. Heidi E. Hamilton is Professor of Linguistics at Georgetown University, USA. She is an expert on the interrelationships between language and health care issues. Her previous works on this topic include Conversations with an Alzheimer's Patient (1994) and Language and Communication in Old Age (1999).